Inteligencia artificial en la educación universitaria: Revisión bibliométrica en Scopus y Web of Science - Tapullima Mori, Calixto; Olivas Ugarte, Lincol Orlando; Carranza Esteban, Renzo Felipe; Mamani Benito, Oscar Javier; Turpo Chaparro, Josué (Revista educare, 2024)
Introduction. Artificial intelligence (AI) today plays an important role in university education; in that sense, the objective of this research is to analyze the scientific production on AI in university education under a bibliometric review in Scopus and Web of Science (WoS). Method. A bibliometric analysis was carried out, where 895 documents published in journals indexed in the Scopus and WoS databases were analyzed. The terms ‘artificial intelligence’, ‘computational intelligence’, ‘AI’, ‘university education’ and ‘university’ were applied as terms, and the Boolean operators AND and OR were used for both databases. Results. We found 848 documents in Scopus and 48 in WoS. China is the country with the highest scientific production. Brain-Broad Research in Artificial Intelligence, Neuroscience, and Education Science are the journals with the highest number of publications in WoS, while in Scopus they are Journal of Physics Conference and Advances in Intelligent Systems and Computing. Regarding the thematic area, it was found that the highest production corresponds to computer science. In terms of affiliation, the authors belong to institutions in China, and the article with the highest number of citations is “Neuropsychological Bases of Self-Improvement of Own Physical Health of Future Teachers in the Course of University Education”. Conclusions. It is necessary to continue research on AI and its implications in university education due to its relevance in the teaching-learning processes and the interdisciplinary innovation that provides tools to reinforce knowledge. Introdução. A inteligência artificial (IA) desempenha hoje um papel importante no ensino universitário e, nesse sentido, o objetivo desta pesquisa é analisar a produção científica sobre IA no ensino universitário por meio de uma revisão bibliométrica na Scopus e na Web of Science (WoS). Método. Foi realizada uma análise bibliométrica na qual foram analisados 895 documentos publicados em periódicos indexados nas bases de dados Scopus e WoS. Foram aplicados os termos ‘artificial intelligence’, ‘computational intelligence’, ‘AI’, ‘university education’ e ‘university’, e os operadores booleanos AND e OR foram utilizados em ambas as bases de dados. Resultados. Encontramos 848 artigos na Scopus e 48 na WoS. A China é o país com a maior produção científica. Brain-Broad Research in Artificial Intelligence, Neuroscience e Education Science são as revistas com o maior número de publicações na WoS, ao passo que na Scopus foram Journal of Physics Conference e Advances in Intelligent Systems and Computing. Com relação à área temática, verificou-se que a maior produção corresponde à ciência da computação. Em termos de afiliação, os autores pertencem a instituições da China e o artigo com o maior número de citações é “Neuropsychological Bases of Self-Improvement of Own Physical Health of Future Teachers in the Course of University Education”. Conclusões. São necessárias mais pesquisas sobre IA e suas implicações na educação universitária, devido à sua relevância nos processos de ensino-aprendizagem e à inovação interdisciplinar que fornece ferramentas para reforçar o conhecimento. Introducción. La inteligencia artificial (IA) hoy juega un papel importante en la educación universitaria; en ese sentido, el objetivo de esta investigación es analizar la producción científica sobre IA en la educación universitaria bajo una revisión bibliométrica en Scopus y Web of Science (WoS). Método. Se realizó un análisis bibliométrico donde se analizaron 895 documentos publicados en revistas indexadas en la base de datos Scopus y WoS. Se aplicaron como términos: ‘artificial intelligence’, ‘computational intelligence’, ‘AI’, ‘university education’ y ‘university’, además se utilizaron los operadores booleanos AND y OR para ambas bases de datos. Resultados. Se encontraron 848 documentos en Scopus y 48 en WoS. China es el país con mayor producción científica, Brain-Broad Research in Artificial Intelligence, Neuroscience y Education Science son las revistas con mayor cantidad de publicaciones en WoS, mientras que en Scopus son Journal of Physics Conference y Advances in Intelligent Systems And Computing. Respecto al área temática, se encontró que la mayor producción corresponde a ciencias de la computación. En cuanto a la filiación, los autores pertenecen a instituciones de China y el artículo con mayor cantidad de citas es “Neuropsychological Bases of Self-Improvement of Own Physical Health of Future Teachers in the Course of University Education”. Conclusiones. Es necesario seguir investigando respecto la IA y sus implicancias en la educación universitaria, debido a su relevancia en los procesos de enseñanza-aprendizaje y la innovación interdisciplinaria que dota de herramientas para reforzar el conocimiento.